THE PROCESSING OF PLASTIC WASTED INTO FUEL OIL IN THE KALANG ANYAR VILLAGE IN SERANG - Efi Tajuroh Afiah; Surachman Surachman; Muhamad Dullaf; Fiki Reynaldi; Ilham Wahyudin (Yayasan Education and Social Center, 2023)
Currently, plastic waste pollution has become a prominent global issue, as well as in Indonesia, where the situation is increasingly concerning. This is likely due to the escalating production of plastic waste, originating from both households and industries, without proper waste management practices. In fact, some studies suggest that if plastic waste production remains unchecked, by 2050, there could be more plastic waste in the oceans than fish. To address this plastic waste problem, various innovations are being pursued by diverse groups, including academics, as an effort to safeguard the Earth for future generations. One such effort involves integrating knowledge with practical activities through the Student Work Lecture Program at Universitas Bina Bangsa, held in the Pekijing Village of Kalang Anyar Subdistrict, Serang City. The outcome of this initiative is that the community gains alternative skills in plastic waste processing to fuel through the student-led activities, with the hope that these skills will eventually be implemented widely in other areas. The technology employed in this process is pyrolysis, where plastic waste is heated at high temperatures and subsequently cooled to extract its oil content. Developments like this aim to enhance the value of waste by transforming it into usable liquid fuel that can benefit daily life, especially in rural communities. Although relatively new in Indonesia, several advanced countries like Japan have already applied similar approaches on an industrial scale. Thus, there is value in fostering early awareness and initiating change at the grassroots level, progressing from villages to a global scale